Between house and agora: gender, space and power in the Greek polis (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The aim of this article is to analyse and reflect on the way how classical Greek society organised through spaces –material and symbolically–, gender differences and hierarchies, as an essential part of the system of the polis. Although genders in classical Greek society were well defined, gender spaces were permeable and flexible; thus we must separate ideal from social practice. In the real life women moved in public spaces; men lived and worked at home; but women and men were not in the same spaces in the same way. Two spaces are especially studied: the male andron in the female house, and the female fountain-house in the male agora. Their location, their physical appearance, their uses, and their symbols, speak to us about the way how were women and men in the society, and reveal spatially the gender relations as relations of power.
Keywords: Gender; space; power; ancient Greece.